Meta Analisis: Validitas dan Praktikalitas Media Pembelajaran E-booklet pada Pembelajaran Biologi - Cemara, Cemara; Zulyusri, Zulyusri (Al-Alam: Islamic Science Education Journal, 2025)
This study aims to analyze the validity and practicality of e-booklets as learning media through a meta-analysis approach. The research method was conducted by reviewing 10 relevant articles published between 2020 and 2025, which were then analyzed based on validity and practicality criteria. The results show that the average validity score of e-booklets reached 91.52%, categorized as very valid, while the average practicality score reached 89.63%, categorized as very practical. The highest validity score was 98.20%, whereas the lowest score was still within the very valid category at 83.30%. Meanwhile, the highest practicality score was 97.73%, and the lowest still fell into the practical category at 79.95%. These findings indicate that e-booklets are feasible to be implemented in biology learning as they meet both validity and practicality standards. In conclusion, e-booklets not only support academic quality but also align with the learning needs of students in the digital era.